2016
DOI: 10.1080/03630269.2016.1190373
|View full text |Cite
|
Sign up to set email alerts
|

Is Vitamin C Supplementation in Patients withβ-Thalassemia Major Beneficial or Detrimental?

Abstract: Globally, β-thalassemia major (β-TM) is one of the most common hereditary disorders. Multiple blood transfusions, that are a life-saving therapy in patients with β-TM, is a major source of iron overload. Iron overload can lead to significant morbidity and mortality. Research evidence indicates that oxidative stress induced by iron overload, is one of the major precipitating causes of vitamin C deficiency in β-TM patients. It has previously been shown that patients with β-TM have significantly lower levels of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…β-Thalassemia Major (β-TM) is the most commonly inherited hemolytic anemia. Patients with β-TM require lifelong adherence to distressing treatment regimen, including regular blood transfusions, daily chelation therapy and frequent medical supervision ( 1 , 2 ). Like other chronic diseases requiring long-life treatment, adherence to treatment is a major concern for β-TM patients ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…β-Thalassemia Major (β-TM) is the most commonly inherited hemolytic anemia. Patients with β-TM require lifelong adherence to distressing treatment regimen, including regular blood transfusions, daily chelation therapy and frequent medical supervision ( 1 , 2 ). Like other chronic diseases requiring long-life treatment, adherence to treatment is a major concern for β-TM patients ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with β-TM require lifelong adherence to distressing treatment regimen, including regular blood transfusions, daily chelation therapy and frequent medical supervision ( 1 , 2 ). Like other chronic diseases requiring long-life treatment, adherence to treatment is a major concern for β-TM patients ( 3 ). It has been revealed that poor adherence to therapeutic regimen in β-TM patients is associated with poor clinical outcomes including increased risk of complications, highest risk of mortality and morbidity and, consequently, increased healthcare costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the absence of an iron chelator, vitamin C can increase iron absorption by reducing Fe 3+ to Fe 2+ , contributes to hydroxyl radical formation and further increases oxidation. Therefore, with its prooxidant activity, vitamin C supplementation in iron-rich conditions is still debatable [ 33 ]. Despite its prooxidant activity, vitamin C increases the efficiency of chelation agents by promoting Fe 2+ and increases the iron release from reticuloendothelial system.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with β-TM require lifelong adherence to distressing treatment regimens, including regular blood transfusions and daily chelation therapy. Therefore, maintaining hemoglobin target levels as well as appropriate chelation therapy has been particularly emphasized in the care of patients with β-TM [ 1 2 ]. In keeping with improvement in life expectancy of β-TM patients, some previously unrecognized health issues have been identified in these patients that affect their quality of life as well as their overall ability to adhere to treatment [ 3 ].…”
Section: Letters To Editormentioning
confidence: 99%